The ultra-hot-Jupiter KELT-16 b: dynamical evolution and atmospheric properties. Issue 1 (21st September 2021) - Mancini, L; Southworth, J; Naponiello, L; Baştürk, Ö; Barbato, D; Biagiotti, F; Bruni, I; Cabona, L; D'Ago, G; Damasso, M; Erdem, A; Evans, D; et al.
ABSTRACT: We present broad-band photometry of 30 planetary transits of the ultra-hot-Jupiter KELT-16 b, using five medium-class telescopes. The transits were monitored through standard $B, \, V, \, R, \, I$ filters and four were simultaneously observed from different places, for a total of 36 new light curves. We used these new photometric data and those from the TESS space telescope to review the main physical properties of the KELT-16 planetary system. Our results agree with previous measurements but are more precise. We estimated the mid-transit times for each of these transits and combined them with others from the literature to obtain 69 epochs, with a time baseline extending over more than 4 yr, and searched for transit time variations. We found no evidence for a period change, suggesting a lower limit for orbital decay at 8 Myr, with a lower limit on the reduced tidal quality factor of $Q^{′ }_{\star }\gt (1.9 ± 0.8) × 10^5$ with $95{{\ \rm per\ cent}}$ confidence. We built up an observational, low-resolution transmission spectrum of the planet, finding evidence of the presence of optical absorbers, although with a low significance. Using TESS data, we reconstructed the phase curve finding that KELT-16 b has a phase offset of 25.25 ± 14.03 °E, a day- and night-side brightness temperature of 3190 ± 61 K and 2668 ± 56 K, respectively. Finally, we compared the flux ratio of the planet over its star at the TESS and Spitzer wavelengths with theoretical emission spectra, finding evidence of a temperature inversion in the planet's atmosphere, the chemical composition of which is preferably oxygen-rich rather than carbon-rich.